Agriculture Cadaster Map of Al-Shehimea - Ghazal, Nawal; Hassoon, Khalid; Abbas, Hashem (Iraqi Journal of Science, 2023)
The cadastral map is very important because it has technical and materialistspecification of the property borders and these maps which are land registrationbased on it in Iraq, the problem is an ancient maps and unfit for use, despite itsimportance, Therefor the updating and digitize the cadastral map is very pivotal, thisis what we have done in the present work.In the present work, we have an old cadastral map (as a paper) was made in 1932with modern satellite image (Quick Bird ) 2006, which has 61 cm resolution for thesame area after. Geometric correction technique has been applied by using image-toimagemethod or (image registration ) and after that we get new agricultural cadastermap and connect them with their own the information for the study area (shehimea)in the medial of Iraq. So that we get new digital cadastral map from old map andsatellite image. This research is carried out by using programs ERDAS and ArcGIS.